It's all about the bike : the pursuit of happiness on two wheels - Penn, Rob (Bloomsbury, 2011)
"The bicycle is one of mankind's greatest inventions and the most popular form of transport in history. Robert Penn has ridden one most days of his adult life. In his late 20s, he pedaled around the world. Yet, like cyclists everywhere, the utilitarian bikes he currently owns don't even hint at this devotion. It's All About the Bike is the story of a journey to design and build a dream bike. En route, Robert explores the culture, science and history of the bicycle. From Stoke in his native UK, where an artisan hand builds his frame, to California, home of the mountain bike, where Robert tracks down the perfect wheels, via Portland, Milan, and back to the UK to Coventry (birthplace of the modern bicycle), this is the narrative of our love affair with cycling. His components set the standard in reliability, craftsmanship and beauty. A cheerful and charming tour guide, Penn tells how the bicycle has changed the course of human history, from the invention of the "people's nag" to the bike's role in the emancipation of women, and from the engineering marvel of the tangent-spoked wheel to the enduring allure of the Tour de France."--